The Generalized Caffarelli‐Kohn‐Nirenberg Theorem for the Hyperdissipative Navier‐Stokes System. Issue 3 (29th August 2019) - Colombo, Maria; De Lellis, Camillo; Massaccesi, Annalisa
Abstract: We introduce a notion of suitable weak solutions of the hyperdissipative Navier‐Stokes equations, and we achieve a corresponding extension of the regularity theory of Caffarelli‐Kohn‐Nirenberg. © 2019 Wiley Periodicals, Inc.